The work of associated scavengers: imbrication between precariousness and self-management - Souza, Diego de Oliveira; Vera Cruz, Ingrid Louise Vieira; Santos, Lucas Barros dos (Argumentum, 2022)
The object of this research is the work of scavengers, especially in their recent collective form, through associations, and what determines the effectiveness of their self-management and the transformation of living and working conditions. It analyzes the opportunities and limits of the work of associated scavengers. In the first part, we carry out a theoretical study, and present the foundations that support the Marxist critique of the current form of associated work, one example of which is the scavengers’ associations. In the second part, we analyze empirical data regarding an association. We carry out the triangulation of three stages of data collection from the association: interviews, focus group and report of extension activities. We found that waste picking activities were an alternative to unemployment and that, although it produced contingencies for survival, it developed imbricated with precariousness.